102k views
0 votes
Given the definitions of f(x) and g(x) below, find the value of g(f(-1)). f(x) = x2 + 7x + 3 g(x) = -4x + 12

User Petrroll
by
5.3k points

1 Answer

3 votes

TO solve this problem first we have to evaluate f(-1)


\begin{gathered} f(-1)=-1^2+7(-1)+3 \\ f(-1)=1-7+3 \\ f(-1)=-3 \end{gathered}

No we evaluete g(-3) so


\begin{gathered} g(-3)=-4(-3)+12 \\ g(-3)=12+12 \\ g(-3)=24 \end{gathered}

User Kris Johnston
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.